Clinical Evaluation of Unilateral Vertebroplasty for OVCF - Xiaoming Wen; Yan Zhang; Wei Jiang; Wenbo An; Binggang Zhang; Jianjun Liu (Emergency Medicine International)
Objective. To investigate the clinical evaluation of unilateral vertebroplasty for OVCF. Methods. A retrospective analysis was performed on 60 patients treated with PVP from January 2020 to December 2021. Patients were divided into two groups according to the treatment method, 30 patients in the PVP group received PVP and 30 patients in the PCVP group received PCVP. The VAS score, ODI score, bone cement dosage, and leakage were compared between the two groups preoperatively, immediately postoperatively, and 7 and 30 days postoperatively. Results. VAS scores in the PCVP and PVP groups before, immediately after, and 7 days after surgery were P>0.05, and the difference was not statistically significant; ODI score in group 1 before surgery was not statistically significant (P>0.05); bone cement injection volume in the PVP group was significantly higher than that in the PCVP group (P<0.05), and the difference was statistically significant; the difference in bone cement leakage between the two groups was not statistically significant (P>0.05). Conclusion. Under the same puncture conditions, the PCVP group used the method of injection while retreating to achieve a better bone cement dispersion effect by using less bone cement and achieving uniform dispersion of bone cement. It can relieve the patients’ back pain and improve the back function.